On-orbit servicing strategies for large constellations via hybrid dynamic programming - Lhuillier, Ignacio Betti; Bellome, Andrea; Felicetti, Leonard (Council of European Aerospace Societies (CEAS), 2024)
The increasing number of mega-constellations inLEOis not only increasing the number of satellites in orbit but potentially might trigger an increment in the amount of space debris. On-orbit servicing is seen as a viable solution to minimize the number of launches needed to maintain these constellations and keep the debris levels low. This paper focuses on trajectory planning for On-Orbit Servicing (OOS) by presenting a novel methodology based on dynamic programming hybridized with deterministic tree search strategies. This is used to schedule the best path for spacecraft to visit satellites that need servicing (such as repair, refueling or repositioning). This methodology is then used to conduct Monte Carlo simulations to study how the main characteristics of the spacecraft affect the performance of the servicing operation. The presented study aims to find the optimal number of servicers needed, the ^V required to perform the operations, and the time of flight between satellites.
Keywords: Dynamic Programming; Beam Search; Multi-target Mission Analysis; Monte Carlo; Tree Exploration